2021
DOI: 10.1186/s12889-021-11216-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived sustainability of the school-based social and behavior change communication (SBCC) approach on malaria prevention in rural Ethiopia: stakeholders’ perspectives

Abstract: Background Evidence on what makes the school-engaged social and behavior change communication (SBCC) interventions on malaria prevention more sustainable are limited in literature partly due to its recent emergence. Enrolling the key stakeholders, this study explored the perceived sustainability of the SBCC interventions on malaria prevention through primary school communities in rural Ethiopia. Methods The SBCC interventions were implemented from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…For most residents, the most common source of information about malaria prevention is mass media (television and radio) and health education by health facilities [ 44 ]. Studies have shown that social and behavior change communication (SBCC) advances individual exposure to malaria messages, acceptance and preventive practices through health education provided to schools or communities, which facilities the control of malaria [ 45 , 46 ]. Delivering customized messages and creating a supportive environment that encourages individuals and communities to adopt positive health behaviors is essential for malaria control [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For most residents, the most common source of information about malaria prevention is mass media (television and radio) and health education by health facilities [ 44 ]. Studies have shown that social and behavior change communication (SBCC) advances individual exposure to malaria messages, acceptance and preventive practices through health education provided to schools or communities, which facilities the control of malaria [ 45 , 46 ]. Delivering customized messages and creating a supportive environment that encourages individuals and communities to adopt positive health behaviors is essential for malaria control [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived susceptibility refers to an individual's perception of the development of illness and diseases due to risk factors [41]. The successful implementation of any public health screening program depends upon the public's awareness of risk factors and their susceptibility to developing diseases [25,42,43]. Some authors evaluated the importance of perceived susceptibility in the breast cancer screening program and revealed that the uptake of breast cancer screening was significantly associated with participants with higher perceived susceptibility [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating a school-based health education intervention in Nepal has identified parental attitudes positively affected the intervention’s feasibility while lack of collaboration with parents was mentioned as a challenge [ 38 ]. A previous similar study (aimed to evaluate the sustainability of the school-based malaria SBCC) showed the negative effects of the factors such as the community’s reluctance and skepticism of the school-based malaria communication [ 20 ]. However, contradicting finding was reported in the other study in which the programme has improved community acceptance of the intervention was reported [ 21 ].…”
Section: Discussionmentioning
confidence: 99%